REVITALISASI PELAYANAN LEMBAGA PENDIDIKAN DASAR - Angga Teguh Prastyo (el-hikmah, 2011)
Movement in growing elementary education becomes a necessity. Moreover, globalisation requirement of high quality education is higher and higher. It attach strings the necessity of fundamental basic in shaping the competence of perfect human. Therefore, the existancy and role of education intitutional need to be strenghtened. Moreover, the expectation people in the world of education continues to rise. This makes basic education institutions to be able to print-based graduates who have the advantage of global and local. Thus, developing a global vision of basic education institutions is an important agenda in the face of globalization. Of course, the desired outcome requires effective education and service learning process measurable. It was a series of learning activities that can help maximize human potential and the interest it has. The learning process becomes one of the key in determining the quality of learning provided to the customer. Therefore, the fundamental need for a paradigm-directed learning process will become one focus of a breakthrough in revitalizing the institution that provided educational services to customers.